BTEX (benzene, toluene, ethylbenzene, and xylene) and risk of cancer - a study from Centers for Disease Control and Prevention's National Health and Nutrition Examination Survey. (9th November 2022) - Malik, P; Hashim, T; Varma, S; Diaz, L; Chowdhary, A; Bapat, P; Alkhatib, L; Centeno, L; Poursina, O; Pan, H; Patil, A
Abstract: Introduction/Objective: BTEX (benzene, toluene, ethylbenzene, and xylene) is well know for its toxicity via through environmental, occupational and recreational exposures. However, there is limited literature about the carcinogenic effect of BTEX. Hence, we aim to study the prevalence and association of cancer amongst individuals with exposure of BTEX. Methods/Case Report: A retrospective cross-sectional study was performed between 2013 and 2018 utilizing the NHANES database. Adult individuals having data on socio-demographic questionnaires and lab findings on exposure to BTEX were included. Prevalence of cancer was identified amongst exposure to BTEX (vs no-BTEX). Univariate (chi-squre test and Mann–Whitney U test) and Multivariate (survey logistic regression) analysis was performed to evaluate the epidemiologic characteristics of individuals exposred to BTEX and association of cancer with BTEX exposure in comparison to no BTEX exposure.The p value of <0.05 considered statistically significant. Results (if a Case Study enter NA): 124, 162 participants were identified with BTEX exposure. Individuals with BTEX exposure were young (40 vs 51 year old), male (91% vs female: 87%), and Mexican American (92% vs Non-Hispanic Black: 89% vs Non-Hispanic White: 89% vs other Hispanic: 87%). Univariate analysis showed higher total prevalence of cancer in BTEX (9.3% vs. 1.3%; p<0.0001) compared to no BTEX. Individuals with BTEX exposure had higher prevalnece of blood cancer (0.47% vs 0.00; p<0.0001), leukemia (0.56% vs 0.00; p<0.001), and lymphoma (1.72% vs 0.39%; p<0.0001) in comparison with no exposure. Multivaritate analysis showed participants with BTEX exposure had 10% higher risk of cancer (aOR: 1.10; 95%CI: 1.10-1.10; p<0.0001) compared to no BTEX exposure. Additionally, exposure to individual components of benzene (aOR: 1.24; 95%CI: 1.24; p<0.0001), ethylbenzene (aOR: 1.08; 95%CI: 1.08-1.08; p<0.0001), and o-xylene (aOR: 1.19; 95%CI: 1.19-1.19; p<0.0001) had higher risk of cancer compared to no exposure participants. Conclusion: Our study conclude higher risk of cancer among participants with exposure to benzene, ethylbenzene and o-xylene. Future studies are warranted to evaluate the association of various types of cancers in BTEX exposure.